Legal Aspects of Government on The Role of The Yosowilangun Village Government in Preserving Local Traditions and Culture - Fidinansyah, Muhammad Iqbal; Wardana, Dodi Jaya (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: Based on the government's efforts to protect, develop, preserve, and utilize the cultural values and heritage of the nation's traditions. The government needs to carry out cultural revitalization to restore and revive marginalized cultural values that could become extinct. In addition to the village government, the community also needs to play a role in preserving traditions and culture to motivate the community to recognize and actively participate in maintaining local cultural heritage.Purposes of the Research: To find out the role and efforts of the village government in developing traditions and culture, in this case the cultural heritage of Yosowilangun Village.Methods of the Research: This study uses a qualitative methodology that includes document analysis, interviews with officers or staff at the Yosowilangun Village Office, and an observational data collection approach. The data analysis method used is interactive analysis, namely data collection and presentation and drawing conclusions.Results Main Findings of the Research: Shows that the Yosowilangun Village Government actively fosters the development of traditions by preserving cultural heritage within the scope of the Yosowilangun Village Government, and strives to overcome existing obstacles in efforts to preserve cultural heritage. Therefore, from the perspective of constitutional law, the role of the Yosowilangun Village Government in maintaining and advancing traditions and culture in accordance with Gresik Regency Regional Regulation Number 8 of 2019, is considered very effective as a foundation for advancing the development of traditions and culture in the Village.